2020
DOI: 10.1111/cas.14411
|View full text |Cite
|
Sign up to set email alerts
|

High expression of Krüppel‐like factor 5 is associated with poor prognosis in patients with colorectal cancer

Abstract: Krüppel‐like factor 5 (KLF5) plays an oncogenic role and has diverse functions in cancer cells. However, correlation between KLF5 and clinical outcome has not been determined in patients with colorectal cancer and colorectal liver metastasis. Herein, we analyzed 65 patients with colorectal cancer who developed colorectal liver metastasis. Clinical effects were assessed through immunohistochemical analysis of primary colorectal cancer lesions and metastatic liver lesions. High expression of KLF5 in these tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 43 publications
1
41
0
Order By: Relevance
“…S8A, B ). Moreover, we and another group recently showed that the treatment of miR-4711-5p targeting to the 3’-UTR of KLF5 mRNA or KLF5 -siRNA attenuated the CSC properties in CRC cell lines [ 10 , 11 ]. We also showed in this study that high KLF5 expression in CRC clinical samples was correlated with poor prognosis, which is consistent with other studies [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S8A, B ). Moreover, we and another group recently showed that the treatment of miR-4711-5p targeting to the 3’-UTR of KLF5 mRNA or KLF5 -siRNA attenuated the CSC properties in CRC cell lines [ 10 , 11 ]. We also showed in this study that high KLF5 expression in CRC clinical samples was correlated with poor prognosis, which is consistent with other studies [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer stem cells (CSCs) are defined as a subpopulation of cancer cells with a self-renewal capacity and multilineage potency and considered a source of tumour recurrence and metastasis [ 9 ]. KLF5 is associated with CSC-like properties because KLF5 knockdown suppressed sphere-formation activity in colorectal cancer (CRC) cell lines [ 10 ]. We also reported that miR-4711-5p, which directly targets the 3’-untranslated regions (3’-UTRs) of KLF5 , suppressed CSC properties in CRC cell lines [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…KLF5 is also a critical mediator of the oncogene H-RAS (18,19) and tumor suppressor APC (20,21). Increases the expression of KLF5 is associated with poor prognosis (22). In vitro knockdown experiments have shown that KLF5 interacts with b-catenin and localizes to the nucleus where the complex transactivates target genes, such as CCND1 and c-MYC (20,22).…”
Section: Discussionmentioning
confidence: 99%
“…Increases the expression of KLF5 is associated with poor prognosis (22). In vitro knockdown experiments have shown that KLF5 interacts with b-catenin and localizes to the nucleus where the complex transactivates target genes, such as CCND1 and c-MYC (20,22). Genome-wide association studies identified the regulatory region of KLF5 as a risk locus for endometrial cancer (23).…”
Section: Discussionmentioning
confidence: 99%
“…Krüppel like factor 5 (KLF5) is a zinc nger transcription factor that contributes to tumor suppression in NPC [8]. However, KLF5 has an oncogenic role in certain types of cancer, such as pancreatic cancer, breast cancer, cervical cancer and colorectal cancer [9][10][11][12]. The miR-493-5p represses the metastasis and proliferation of osteosarcoma cells by targeting KLF5 [13].…”
Section: Introductionmentioning
confidence: 99%